Cooking the remainig words. An analysis of linguistic and culinary practices of the Borán people - Cisneros Vargas, Nicole (2021)
Traditions and language of a people generally reflect its conception of the world and show the conditions in which it has developed; in order to identify these elements in the indigenous community of Brorán, located in the province of Puntarenas, Costa Rica, this article analyze the most frequent ingredients, the culinary techniques and the final presentation of the recipes documented in Diccionario-recetario pictográfico de la alimentación tradicional en Brörán̈ qu’ercuó (the Terraba language) to categorize the culinary process of this indigenous people based on the notions of Claude Lévi-Strauss.